Social support modifies the association between hazardous drinking and depression symptoms among ART clients in Vietnam. (1st October 2020) - Nguyen, M.X.; Dowdy, D; Latkin, C.A.; Hutton, H.E.; Chander, G; Frangakis, C; Lancaster, K.E.; Sripaipan, T; Bui, Q.X.; Tran, H.V.; Go, V.F.
Highlights: Hazardous drinking and depression symptoms were common among ART clients in Vietnam. Hazardous drinking was significantly associated with depressive symptoms in the sample. Social support modified the association between hazardous drinking and depression symptoms. When social support was low, hazardous drinking increased the likelihood of depression symptoms by 71 %. Abstract: Introduction: Hazardous drinking is widespread among people with HIV (PWH). PWH are also vulnerable to depression due to HIV-related social stigma, and social support can play an important role in improving mental health for this population. No studies have explored whether social support modifies the association of hazardous drinking and depressive symptoms among PWH. Methods: We used baseline data from a randomized controlled trial of two evidence-based alcohol reduction interventions among antiretroviral therapy clients in Vietnam. Hazardous alcohol use was defined as having a score ≥8 for men and ≥ 7 for women on the Alcohol Use Disorders Identification Test. The presence of depression symptoms was defined as a score ≥ 5 on the Patient Health Questionnaire-9. Social support was measured with a 5-question modified version of the Medical Outcomes Study Social Support Instrument. Crude (CPRs) and adjusted prevalence ratios (aPRs) of the association were presented. Results: Hazardous drinking was significantly associated with increased likelihood of having depressive symptoms (aPR = 1.26;95%CI 1.04−1.52). Hazardous drinking and depression symptoms were not associated among those with high social support (aPR = 1.01;95%CI 0.76–1.35), but were associated among those with medium (aPR = 1.24;95%CI 0.92–1.69) and low social support (aPR = 1.71;95%CI 1.25–2.34). Conclusions: Social support significantly modified the association between hazardous drinking and depression symptoms among ART clients in Vietnam. Interventions to decrease hazardous alcohol use are broadly indicated for PWH in Vietnam and other low-resource settings, but special attention or modifications may be needed to support mental health among those with lower levels of social support.